Risk of lead explantation after first-time implantation of cardiac implantable electronic device as a function of comorbidity: a nationwide study. (3rd October 2022) - Alhakak, A; Philbert, B T; Risum, N; Mogensen, U M; Jons, C; Jacobsen, P K; Haarbo, J; Johansen, J B; Nielsen, J C; Riahi, S; Torp-Pedersen, C; Fosbol, E L; et al.
Abstract: Background: The benefit of cardiac implantable electronic devices (CIEDs) is challenged by the risk of procedure-related complications and lead explantation. Whether patient comorbidity burden is associated with risk of lead explantation <6 months of implantation is unknown. Purpose: We assessed the risk of lead explantation and its association with comorbidity burden within 6 months after first-time CIED implantation. Methods: The study population comprised patients ≥18 years old with first-time CIED implantation (i.e., pacemaker [PM], implantable cardioverter defibrillator [ICD], and cardiac resynchronisation therapy with defibrillator [CRT-D] or without [CRT-P]) using Danish nationwide registries including the Danish Pacemaker and ICD registry (1 January 2000 to 30 June 2018). Patients were followed from their first-time CIED implantation and 6 months forward. Patient comorbidity burden was categorised in four groups according to the Charlson Comorbidity Index (CCI) score: 0 (none), 1–2 (mild), 3–4 (moderate), and ≥5 (severe). Multivariable cause-specific Cox regression was performed to assess risk of lead explantation according to comorbidity burden, with death as competing risk. Comorbidity burden was adjusted for sex, age, type of CIED, and body mass index categories. Results: We identified 73, 491 patients with first-time CIED implantation including 55, 733 (75.8%) with PM, 11, 351 (15.5%) with ICD, 2, 989 (4.1%) with CRT-P, and 3, 418 (4.7%) with CRT-D. In total, 1, 049 (1.4%) patients underwent lead explantation. The median age of the study population was 75.1 years [25th-75th percentile 66.2–82.5 years], and 62.1% were male. Patients undergoing lead explantation had higher median CCI score, compared with those not undergoing lead explantation (2 [1–3] and 1 [0–3], respectively). The median age and distribution of sex were similar in both groups. In the multivariable Cox regression model (Figure 1), an increase in patient comorbidity burden was associated with higher hazard ratio [HR] of lead explantation, compared with CCI score 0 (CCI score 1–2: HR=1.38 [95% confidence interval [CI]: 1.12–1.69], CCI score 3–4: HR=1.61 [95% CI: 1.28–2.03], and CCI score ≥5: HR=1.60 [95% CI: 1.25–2.05]). Conclusion: Risk of lead explantation within 6 months after first-time implantation of cardiac implantable electronic device was 1.4% and associated with higher comorbidity burden. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Independent Research Fund Denmark